The deterrent effect of capital punishment in the five most active execution states: a time series analysis - Decker, Scott H. (Criminal justice review, 1990)
This study examines the effect of the death penalty on the murder rate. A 50-year time series is employed for the period 1930-1980 for the five states with the largest number of executions during this period: Georgia, New York, Texas, California, and North Carolina. Taken together, these five states accounted for 40 percent of all the executions performed during this period. Incorporating a lag structure for the effect of executions, as well as several theoretically relevant explanatory variables for homicides, the study identifies no deterrent effect for executions. Several different policy-relevant analyses are performed, all with the same result. Neither the existence of the death penalty, its imposition, nor the level of imposition explains significant amounts of the variation in homicide rates in the 50-year period, 1930 to 1980